A Commentary on the United Nations Convention on the Rights of the Child, 31 : the Right to Leisure, Play and Culture. - David, Paulo (BRILL, 2006)
Constitutes a commentary on Article 31 of the United Nations Convention on the Rights of the Child. Part of the series, "A Commentary on the United Nations Convention on the Rights of the Child", this work provides an article by article analysis of substantive, organizational and procedural provisions of the CRC and its two Optional Protocols.